(3MGhi Gdafhf hSdhI GdeMPhbs - (3CHhGdMSf eMeO Hf GdMSfs; (3GHf GdWMGf GdehSibjs
(3ChdgG (B:s
(3GdebGdI GdKGfjI ai GdUfGYg adh COQcgG CMO HdG WHY dCOQcgG YdhjI , eY MPbI hMSf YJGFg s
(3BNQgG (B:s
(3Ke cJGH MGhi Gdafhf hSdhI GdeMPhb hGdMeO ddg hdi GdMeO , hGdeGf Hg Ydi cd MQ hYHO s
(3GdKGfjg Yedjg hajgG (B22 (3HGHkGs
(3QJHg Ydi ebGdJjf(B: (3GdChdi Ydejg hajgG (B80 (3HGHkGs
(3fSNI CKQjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B51 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdehSjbi hGdZfGAs